Design of an Improved Cooking Stove Using High Density Heated Rocks and Heat Retaining Techniques - Bantu, Anthony A.; Nuwagaba, Gilbert; Kizza, Sarah; Turinayo, Yonah K. (Journal of Renewable Energy, 2018)
In sub-Saharan Africa, dependence on wood fuel has caused significant depletion of vegetative resources. Whereas there exist hundreds of improved cooking stoves, many have not reached their maximum potential because their designs are predominantly focused on either fuel efficiency or reduced smoke. This research designed and fabricated an improved charcoal stove using high density rocks and heat retaining techniques. The aim was to retain heat and minimise heat losses in cooking devices with a sole purpose of reducing the amount of fuel used during cooking. The stove design herein incorporates the interaction of physical and thermal properties of granite rocks with heat loss theories to give a thermal efficient unit. The stove was estimated to cost US$ 36 which compared favourably with most of the improved charcoal stoves on international market (US$ 3–50 US$). This study revealed that, by introducing the new stove design and insulation, the granite rocks depicted high thermal storage properties with potential for reducing fuel use by over 78% with reference to the open fire stove. The designed granite rock stove therefore paves way for the use of high density rocks in improved cook stoves to achieve high performance energy efficient systems that can sustainably put to use vegetative resources.